The Influence of Job Satisfaction, Work Environment and Workload on Loyalty of National Sharia Bank Employees - Sarwo Hakim; Tri Endar Susianto; Sukma Irdiana; Yudiyanto Joko Purnomo; Hery Purnomo (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of this study is to ascertain how employee loyalty is impacted by workload, work environment, and job satisfaction. The national sharia bank at Indonesia's headquarters served as the research site for this study, which employed a quantitative methodology. Only 100 permanent employees were utilized as the sample in this study, which used incidental sampling and the Slovin technique to determine the number of responders. A questionnaire was utilized to collect data, which was then subjected to route analysis for analysis. The findings of this study suggest that Workload and Work Environment, two paths or sub-structural factors, have a considerable, simultaneous, or partial impact on Job Satisfaction. Path 2, or sub-structural 2, has as a result that Workload, Work Environment, and Job Satisfaction have a strong, simultaneous, and partial impact on Employee Loyalty.